Method for removing residual fluorescent liquid before welding of part
By using a combination of hyperbranched polymer grafted modified activated carbon and modified bentonite, combined with ultrasonic wave and heating treatment, the problem of residual fluorescent liquid in complex structural parts is solved, and the fluorescent liquid in the surface and gaps of the parts is thoroughly realized Remove, reducing the number of cleanings.
Patent Information
- Application Number
- CN202411300089.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art is difficult to effectively remove the residual fluorescent liquid in the surface and gaps of complex structural parts, especially during the flushing process, which makes it difficult to completely remove the fluorescent liquid, resulting in repeated cleaning.
Use hyperbranched polymer grafted modified activated carbon and modified bentonite as cleaning agents, combined with ultrasonic cleaning and heating treatment, and use its powerful adsorption and chelation to remove fluorescent liquid, and reduce bubble generation through sodium gluconate to improve cleaning efficiency .
It realizes the complete removal of fluorescent liquid in the surface and gaps of the parts at one time, reduces repeated cleaning work, and improves cleaning efficiency and effect.
Smart Images

Figure CN119194458A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of parts processing, and in particular to a method for removing residual fluorescent liquid before parts welding. Background Art
[0002] After the existing products are inspected by fluorescent flaw detection before welding, the fluorescent liquid on the surface of the products needs to be removed. At present, the commonly used removal methods are: ultrasonic cleaning and tap water washing, but for parts with complex structures, the fluorescent liquid still cannot be effectively removed, and residual fluorescent liquid will penetrate from the gaps of the products.
[0003] Patent No. CN101887031A discloses a fluorescent penetrant detection method, which involves flushing the workpiece with water at a certain pressure at 10-38°C to remove the penetrant. However, the penetrant has a certain adsorption to the workpiece, and in particular, the penetrant located in the gaps of the workpiece is difficult to clean with water, and the penetrant removal effect is poor.
[0004] Fluorescent liquid refers to penetrant and developer. The penetrant includes secondary chain alkane polyether, ethoxylated and propoxylated C6-10 alcohol, alkoxy polyethylene oxyethanol, etc. Ethoxylated and propoxylated C6-10 alcohol and alkoxy polyethylene oxyethanol have only certain solubility in water; the developer includes pentaerythritol, magnesium carbonate, aluminum oxide and other materials. Magnesium carbonate and aluminum oxide are difficult to dissolve in water. During the inspection process, the developer and penetrant will be adsorbed on the gaps or surfaces of the parts, and it is difficult to rinse them clean with running water. The rinsing effect is poor for complex parts and the cleaning time is long. Summary of the invention
[0005] The purpose of the present invention is to provide a method for removing residual fluorescent liquid before welding of parts, which can completely remove the fluorescent liquid that is difficult to remove in the pores of the parts at one time, thereby helping to reduce repeated cleaning work.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for removing residual fluorescent liquid before welding a part comprises the following steps:
[0008] (1) Heat and cool the parts after preliminary washing;
[0009] (2) Place the cooled parts in an ultrasonic cleaning machine, add a cleaning agent, shake them, and then rinse them with clean water;
[0010] (3) Dry the rinsed parts until there is no fluorescent reaction when exposed to black light;
[0011] The cleaning agent comprises, by weight: 10-20 parts of hyperbranched polymer grafted modified activated carbon, 10-15 parts of modified bentonite and 3-7 parts of sodium gluconate.
[0012] The technical solution of the present invention has at least the following advantages and beneficial effects:
[0013] In the present invention, the hyperbranched polymer grafted modified activated carbon has a highly branched three-dimensional spherical structure, contains a large amount of pores in the molecule, improves the adsorption performance of activated carbon on the one hand, increases the active site of adsorbed material on the other hand, helps to adsorb organic substances such as alcohols and ethers in fluorescent liquid. Hyperbranched polymer also has abundant terminal functional groups (carboxyl, amino, etc.), which can form coordination bonds with metal ions, realize chelation, and complete the removal of metal ions in the developer. Loading phosphoric acid on activated carbon can promote chelation reaction, and the active components specifically loaded on activated carbon are mainly H3PO4, H4P2O7 and other materials. Phosphoric acid exists in various forms on activated carbon, and phosphoric acid of different forms has different proton-donating abilities, and the degree of ionization of acid is proportional to the proton-donating ability, and the more protons provided, the better the catalysis. After phosphoric acid is ionized, it reacts with magnesium carbonate and aluminum oxide in the developer to generate magnesium ions and aluminum ions, which promote chelation with the hyperbranched polymer, thereby accelerating the removal of magnesium carbonate, aluminum oxide and other doped metal ions. Due to the different degrees of ionization of different phosphoric acids, it can continuously provide catalysis, which has a better effect on the removal of fluorescent liquid.
[0014] Modified bentonite includes inorganic modification and organic modification. In the inorganic modification process, Ti is selected 4+Polyhydroxy cations are used as pillaring agents. First, the metal ion salts are hydrolyzed with alkali to obtain oligohydroxy cations as pillaring liquid; then the oligohydroxy cations in the pillaring liquid are exchanged into the bentonite interlayer by using the cation exchange effect of bentonite; finally, porous columnar metal oxides are formed between the layers by heating and dehydroxylation, and inorganic pillared bentonite is obtained, which can expand the interlayer spacing, increase the specific surface area, form a two-dimensional pore network structure between the layers, increase the adsorption space, and improve its adsorption effect. In the organic modification process, the presence of hydroxyl groups on the surface of bentonite is used, and organic silane is selected as a coupling agent. The methoxy group in the silane reacts with the hydroxyl group on the surface of bentonite to introduce the required specific functional organic groups such as thiol and amino groups by grafting, so as to achieve the purpose of bonding the organic groups on the surface of bentonite, so that the bentonite is transformed into lipophilic and hydrophobic, and the adsorption capacity is enhanced. At the same time, the thiol and amino groups provide active centers for chelating with metal ions and combining with inorganic and organic pollutants, thereby effectively removing the fluorescent liquid. The combination of hyperbranched polymer grafted modified activated carbon and modified bentonite, the former removes fluorescent liquid through its powerful adsorption and chelation, and the latter removes fluorescent liquid through adsorption and flocculation, can form a complementary adsorption system that can simultaneously process multiple substances in the fluorescent liquid and improve the removal effect of the fluorescent liquid.
[0015] Since the fluorescent liquid contains a variety of surfactants, it is easy to generate foam during the ultrasonic oscillation process, and too much foam will affect the ultrasonic cleaning effect. Sodium gluconate, as a cleaning agent component, can significantly reduce the generation of bubbles without affecting the cleaning effect, and is pollution-free and harmless; sodium gluconate is also a good all-round chelating agent, which has a good chelating ability for a variety of metal ions and can also effectively remove rust. Sodium gluconate solves the following defects: During the parts cleaning process, excessive foam will not only weaken the mechanical action, reduce the cleaning efficiency, and cause a large loss of cleaning fluid, but also cause damage to the equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 A schematic diagram of fluorescence detection of a part after cleaning once using the method of the embodiment;
[0017] Figure 2 This is a schematic diagram of fluorescence detection of parts with obvious fluorescence after cleaning;
[0018] Figure 3 This is a schematic diagram of fluorescence detection showing obvious fluorescence after parts are cleaned. DETAILED DESCRIPTION
[0019] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0020] A method for removing residual fluorescent liquid before welding a part comprises the following steps:
[0021] (1) Heat and cool the parts after preliminary washing;
[0022] (2) Place the cooled parts in an ultrasonic cleaning machine, add a cleaning agent, shake them, and then rinse them with clean water;
[0023] (3) Dry the rinsed parts until there is no fluorescent reaction when exposed to black light;
[0024] The cleaning agent comprises, by weight: 10-20 parts of hyperbranched polymer grafted modified activated carbon, 10-15 parts of modified bentonite and 3-7 parts of sodium gluconate.
[0025] Preliminary flushing can remove residual fluorescent liquid and other impurities on the surface of parts. Heating treatment can volatilize some substances and destroy the components of the penetrant with the help of high temperature, making it easier to clean the penetrant in the gaps and inner cavities, thereby improving the cleaning effect.
[0026] The parts are ultrasonically cleaned under the action of a cleaning agent. The hyperbranched polymer grafted modified activated carbon has a highly branched three-dimensional spherical structure and contains a large number of pores in the molecule. On the one hand, it improves the adsorption performance of the activated carbon, and on the other hand, it increases the active sites of the adsorbed substances, which is helpful for the adsorption of organic substances such as alcohols and ethers in the fluorescent liquid. The hyperbranched polymer also has abundant terminal functional groups (carboxyl, amino, etc.), which can form coordination bonds with metal ions to achieve chelation and complete the removal of metal ions in the developer. The phosphoric acid loaded on the activated carbon can promote the chelation reaction. The specific active components loaded on the activated carbon are mainly H3PO4, H4P2O7 and other substances. Phosphoric acid exists in various forms on the activated carbon. Different forms of phosphoric acid have different proton-donating abilities, and the degree of acid ionization is proportional to the proton-donating ability. The more protons are given, the better the catalytic effect. After phosphoric acid is ionized, it reacts with magnesium carbonate and aluminum oxide in the developer to generate magnesium ions and aluminum ions, which promote chelation with the hyperbranched polymer, thereby accelerating the removal of magnesium carbonate, aluminum oxide and other doped metal ions. Due to the different degrees of ionization of different phosphoric acids, it can continuously provide catalysis, which has a better effect on the removal of fluorescent liquid.
[0027] Modified bentonite includes inorganic modification and organic modification. In the inorganic modification process, Ti is selected 4+Polyhydroxy cations are used as pillaring agents. First, the metal ion salts are hydrolyzed with alkali to obtain oligohydroxy cations as pillaring liquid; then the oligohydroxy cations in the pillaring liquid are exchanged into the bentonite interlayer by using the cation exchange effect of bentonite; finally, porous columnar metal oxides are formed between the layers by heating and dehydroxylation, and inorganic pillared bentonite is obtained, which can expand the interlayer spacing, increase the specific surface area, form a two-dimensional pore network structure between the layers, increase the adsorption space, and improve its adsorption effect. In the organic modification process, the presence of hydroxyl groups on the surface of bentonite is used, and organic silane is selected as a coupling agent. The methoxy group in the silane reacts with the hydroxyl group on the surface of bentonite to introduce the required specific functional organic groups such as thiol and amino groups by grafting, so as to achieve the purpose of bonding the organic groups on the surface of bentonite, so that the bentonite is transformed into lipophilic and hydrophobic, and the adsorption capacity is enhanced. At the same time, the thiol and amino groups provide active centers for chelating with metal ions and combining with inorganic and organic pollutants, thereby effectively removing the fluorescent liquid. The combination of hyperbranched polymer grafted modified activated carbon and modified bentonite, the former removes fluorescent liquid through its powerful adsorption and chelation, and the latter removes fluorescent liquid through adsorption and flocculation, can form a complementary adsorption system that can simultaneously process multiple substances in the fluorescent liquid and improve the removal effect of the fluorescent liquid.
[0028] As a cleaning agent component, sodium gluconate can significantly reduce the generation of bubbles without affecting the cleaning effect, and is pollution-free and harmless; sodium gluconate is also a good all-round chelating agent, which has a good chelating ability for a variety of metal ions and can effectively remove rust. Heating during the oscillation process can accelerate the emulsification of surfactants, improve the adsorption performance of each component in the cleaning agent, and increase the cleaning speed of residual fluorescent liquid and other impurities. Among them, the cleaning agent is first dispersed in water to make a dispersion, and then the dispersion is added to the ultrasonic cleaning machine to ultrasonically clean the parts.
[0029] Furthermore, in step (2), after adding the cleaning agent and shaking for 20-30 minutes, 2-5 parts by weight of an inorganic alkaline substance are added and the shaking is continued.
[0030] Since parts may produce oil stains during the fluorescence detection process, inorganic alkaline substances provide an alkaline environment, allowing the oil and inorganic alkaline substances to react to form carboxylates and glycerol, thereby becoming soluble substances to be removed. At the same time, the surfactant will emulsify during the ultrasonic process, which can emulsify the viscous oil stains, thereby stripping the oil stains from the parts and playing a cleaning role.
[0031] During the cleaning process, the cleaning agent is first used to provide an acidic environment, which is used to convert the insoluble compounds in the fluorescent liquid into water-soluble compounds, and to chelate the metal ions with the hyperbranched polymer grafted modified activated carbon, modified bentonite and sodium gluconate to improve the removal effect of metal ions. Then, the inorganic alkaline substance is used to neutralize the acid and react with the grease to remove the grease on the surface of the parts, thereby improving the cleanliness of the parts.
[0032] Furthermore, the inorganic alkaline substance includes one or more of sodium silicate, sodium metasilicate pentahydrate and sodium hydroxide. Sodium metasilicate pentahydrate is preferred, which can neutralize acidic substances and emulsify fats and oils. At the same time, the silicate ions in the sodium metasilicate pentahydrate molecules can form a chemical bond with the metal surface, so that the sodium metasilicate pentahydrate molecules can be firmly adsorbed on the metal surface, providing anti-corrosion protection for metal parts.
[0033] Further, the modification steps of the modified activated carbon include (a) pretreatment of activated carbon: sequentially impregnating the activated carbon with sodium hydroxide solution and hydrochloric acid, then adding the activated carbon into a nitric acid solution, heating in a water bath for 3 hours, cooling, and drying; (b) loading of activated carbon: mixing the activated carbon with silica sol, keeping the temperature at 80°C for 3 hours, impregnating for 24 hours, and drying, and then mixing with a phosphoric acid solution, keeping the temperature at 80°C for 3 hours, impregnating for 24 hours, and drying. The mass ratio of activated carbon, silica sol, and phosphoric acid is 1:0.2:0.4.
[0034] Furthermore, the modification steps of the modified bentonite include (a) inorganic modification: adding bentonite to a TiCl4 solution, stirring, heating, and drying; (b) organic modification: mixing the bentonite treated in step (1) with a toluene solution of γ-mercaptopropyltrimethoxysilane, stirring and refluxing for 10 hours, filtering, washing with toluene, refluxing with ethanol for 24 hours, and vacuum drying at 100°C for 2 hours. Wherein, bentonite: γ-mercaptopropyltrimethoxysilane: toluene = 1g: 5mmol: 50mL.
[0035] Furthermore, in step (1), during the heating treatment, the temperature is heated to 200-260° C. for 1-2 hours.
[0036] Furthermore, in step (2), the shaking treatment temperature is 40-50°C, the time is 1-2h, and the mixture is rinsed with clean water for 3-10min.
[0037] Example 1
[0038] A method for removing residual fluorescent liquid before welding a part comprises the following steps:
[0039] (1) Heat the parts after preliminary washing to 240°C for 1.5 hours and cool;
[0040] (2) Place the cooled parts in an ultrasonic cleaning machine, disperse the cleaning agent in water to make a dispersion, then add the dispersion and shake for 30 minutes, then add 3g of sodium metasilicate pentahydrate and continue shaking for 30 minutes at a shaking temperature of 45°C, and rinse with clean water for 5 minutes;
[0041] (3) Place the rinsed parts in a 260°C oven to dry, cool, and irradiate with a black light until there is no fluorescent reaction.
[0042] The cleaning agent comprises: 15g of hyperbranched polymer grafted modified activated carbon, 10g of modified bentonite and 5g of sodium gluconate, which are mixed to obtain the cleaning agent.
[0043] The modification steps of the modified activated carbon include (a) pretreatment of the activated carbon: sequentially impregnating the activated carbon with a sodium hydroxide solution and hydrochloric acid, then adding the activated carbon into a nitric acid solution, heating it in a water bath for 3 hours, cooling it, and drying it; (b) loading the activated carbon: mixing the activated carbon with silica sol, keeping it at a constant temperature of 80°C for 3 hours, impregnating it for 24 hours, and then drying it, and then mixing it with a phosphoric acid solution, keeping it at a constant temperature of 80°C for 3 hours, impregnating it for 24 hours, and drying it. The mass ratio of the activated carbon, silica sol, and phosphoric acid is 1:0.2:0.4.
[0044] The modification steps of the modified bentonite include (a) inorganic modification: adding bentonite to a TiC l4 solution, stirring, heating, and drying; (b) organic modification: mixing the bentonite treated in step (1) with a toluene solution of γ-mercaptopropyltrimethoxysilane, stirring and refluxing for 10 hours, filtering, washing with toluene, refluxing with ethanol for 24 hours, and vacuum drying at 100°C for 2 hours. Wherein, bentonite: γ-mercaptopropyltrimethoxysilane: toluene = 1g: 5mmol: 50mL.
[0045] Example 2
[0046] A method for removing residual fluorescent liquid before welding a part comprises the following steps:
[0047] (1) Heat the parts after preliminary washing to 200°C for 2 hours and cool;
[0048] (2) Place the cooled parts in an ultrasonic cleaning machine, disperse the cleaning agent in water to make a dispersion, then add the dispersion and shake for 20 minutes, then continue shaking for 50 minutes with 5g of sodium silicate at a shaking temperature of 50°C, and rinse with clean water for 10 minutes;
[0049] (3) Place the rinsed parts in a 200°C oven to dry, cool, and irradiate with a black light until there is no fluorescent reaction.
[0050] The cleaning agent comprises: 20g of hyperbranched polymer grafted modified activated carbon, 12g of modified bentonite and 7g of sodium gluconate, which are mixed to obtain the cleaning agent.
[0051] Example 3
[0052] A method for removing residual fluorescent liquid before welding a part comprises the following steps:
[0053] (1) Heat the parts after preliminary washing to 260°C for 1 hour and cool;
[0054] (2) Place the cooled parts in an ultrasonic cleaning machine, disperse the cleaning agent in water to make a dispersion, then add the dispersion and shake for 25 minutes, then add 2g of sodium silicate, sodium metasilicate pentahydrate and sodium hydroxide and continue shaking for 60 minutes at a shaking temperature of 40°C, and rinse with clean water for 3 minutes;
[0055] (3) Place the rinsed parts in a 250°C oven to dry, cool, and irradiate with a black light until there is no fluorescent reaction.
[0056] The cleaning agent comprises: 10g of hyperbranched polymer grafted modified activated carbon, 15g of modified bentonite and 3g of sodium gluconate, which are mixed to obtain the cleaning agent.
[0057] Comparative Example 1
[0058] The cleaning agent of this comparative example does not include the hyperbranched polymer grafted modified activated carbon. The rest is the same as that of Example 1.
[0059] Comparative Example 2
[0060] The cleaning agent of this comparative example does not include modified bentonite. The rest is the same as that of Example 1.
[0061] Comparative Example 3
[0062] The activated carbon was not modified in the cleaning agent of this comparative example. The rest was the same as that of Example 1.
[0063] Comparative Example 4
[0064] The bentonite was not modified in the cleaning agent of this comparative example. The rest was the same as that of Example 1.
[0065] Comparative Example 5
[0066] The removal method in this comparative example is: firstly, an inorganic alkaline substance is added for ultrasonic oscillation treatment, and then a cleaning agent is added for further ultrasonic oscillation treatment. The rest is the same as in Example 1.
[0067] Test results
[0068] The parts were cleaned by the methods of the embodiment and the comparative example, and the cleaning times were 1 time, 2 times, and 3 times. After each cleaning, the parts were subjected to fluorescence detection. The results are as follows:
[0069] Table 1 Fluorescence detection results
[0070]
[0071]
[0072] According to Table 1 and Figure 1 It can be seen that after the parts of Examples 1-3 were cleaned once, there was no fluorescence on the surface, indicating that the fluorescent liquid on the parts can be completely removed by cleaning the parts once using the method of the embodiment, and the cleaning effect is good.
[0073] according to Figure 2-3 It can be seen that, compared with Example 1, the fluorescent liquid removal effect on the parts in Comparative Examples 1-4 is poor, and there is obvious or relatively obvious fluorescence on the parts. This shows that the use of hyperbranched polymer grafted modified activated carbon and modified bentonite can enhance the cleaning effect of the cleaning agent and improve the cleaning efficiency.
[0074] Compared with Example 1, in Comparative Example 5, the parts are first cleaned in an acidic environment and then cleaned in an alkaline environment, which can improve the cleaning efficiency.
[0075] In summary, the method for removing residual fluorescent liquid before welding of parts provided by the present invention can completely remove the fluorescent liquid that is difficult to remove from the pores of parts at one time, which helps to reduce repeated cleaning work.
[0076] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for removing residual fluorescent liquid from parts before welding, characterized in that: The following steps are involved: (1) Heat and cool the parts after preliminary washing; (2) Place the cooled parts in an ultrasonic cleaning machine, add a cleaning agent, shake them, and then rinse them with clean water; (3) Dry the rinsed parts until there is no fluorescent reaction when exposed to black light; The cleaning agent comprises, by weight: 10-20 parts of hyperbranched polymer grafted modified activated carbon, 10-15 parts of modified bentonite and 3-7 parts of sodium gluconate.
2. The method for removing residual fluorescent liquid from parts before welding according to claim 1, characterized in that: In step (2), after adding the cleaning agent and shaking for 20-30 minutes, 2-5 parts by weight of an inorganic alkaline substance are added and the shaking is continued.
3. The method for removing residual fluorescent liquid before welding of parts according to claim 2, characterized in that: The inorganic alkaline substance includes one or more of sodium silicate, sodium metasilicate pentahydrate and sodium hydroxide.
4. The method for removing residual fluorescent liquid before welding of parts according to claim 1, characterized in that: The modification steps of the modified activated carbon include (a) pretreatment of the activated carbon: sequentially impregnating the activated carbon with a sodium hydroxide solution and hydrochloric acid, then adding the activated carbon into a nitric acid solution, heating it in a water bath for 3 hours, cooling it, and drying it; (b) loading the activated carbon: mixing the activated carbon with silica sol, keeping the temperature at 80°C for 3 hours, impregnating it for 24 hours, and then drying it, then mixing it with a phosphoric acid solution, keeping the temperature at 80°C for 3 hours, impregnating it for 24 hours, and drying it.
5. The method for removing residual fluorescent liquid from parts before welding according to claim 1, characterized in that: The modification steps of the modified bentonite include (a) inorganic modification: adding bentonite to a TiCl4 solution, stirring, heating and drying; (b) organic modification: mixing the bentonite treated in step (1) with a toluene solution of γ-mercaptopropyltrimethoxysilane, stirring and refluxing for 10 hours, filtering, washing with toluene, refluxing with ethanol for 24 hours, and vacuum drying at 100°C for 2 hours.
6. The method for removing residual fluorescent liquid before welding of parts according to claim 1, characterized in that: In step (1), during the heating treatment, the temperature is heated to 200-260° C. for 1-2 hours.
7. The method for removing residual fluorescent liquid before welding of parts according to claim 1, characterized in that: In step (2), the shaking treatment temperature is 40-50°C, the time is 1-2 hours, and the mixture is rinsed with clean water for 3-10 minutes.
Citation Information
Patent Citations
Fluorescent penetrant detecting method
CN101887031A
Cited By
Method for removing fluorescent substances on surface of welded corrugated pipe
CN121551337A
A method for removing surface fluorescence from a welded corrugated pipe
CN121551337B
